Distinct Differences in Emotional Recognition According to Severity of Psychotic Symptoms in Early-Stage Schizophrenia - Won, Seunghee; Lee, Won Kee; Kim, Sung-Wan; Kim, Jung Jin; Lee, Bong Ju; Yu, Je-Chun; Lee, Kyu Young; Lee, Seung-Hwan; Kim, Seung-Hyun; Kang, Shi Hyun; Kim, Euitae; Chung, Young-Chul (Frontiers in Psychiatry, 2019)
Patients with schizophrenia are characterized by deficits in their ability to identify facial expressions of emotion, which are associated with impaired social and occupational function. An understanding of the deficits of facial affect recognition (FAR) early in the course of the illness can improve early intervention efforts to ameliorate potential functional deterioration. This study aimed to investigate the characteristics and correlations between psychotic symptoms and FAR deficits in patients with early-stage schizophrenia using data from the Korean Early Psychosis Cohort Study. Patients with schizophrenia were divided into three groups: 1) severely and markedly ill (n=112), 2) moderately ill (n=96), and 3) mildly ill (n=115). These groups were compared with age- and sex-matched healthy controls. The FAR test was developed using Korean emotional faces from the Korean Facial Expressions of Emotion database. Error rates, correct response times, and non-response rates of each subset were calculated. Several psychopathology assessments were also performed. There were significantly more deficits associated with the recognition of anger (p<0.01), fear (p<0.01), and contempt (p<0.01) in the three patient groups than in the healthy control group. In the severely and markedly ill states, all emotions apart from surprise had impaired error rates (p<0.01 for all analyses) The error rates for happiness, sadness, disgust, surprise, and neutral faces were not significantly different between mildly ill patients and healthy controls. All emotions, except for sadness, had significantly more delayed correct response times in all patient groups than in the healthy controls (p<0.01 for all analyses). The severity of psychotic symptoms was positively correlated with the happiness and neutral error rates, and depression was positively correlated with the happiness error rates. General social function was negatively correlated with the error rates for happiness, sadness, fear, disgust, and surprise. Overall, our results show that the severity of psychosis and clinical symptoms lead to distinct differences in certain emotions of patients with early-stage schizophrenia. It is considered that these specific emotional characteristics will help deepen our understanding of schizophrenia and contribute to early intervention and recovery of social function in patients with schizophrenia.